Pengaruh Status Sosial Ekonomi Orang Tua dan Literasi Keuangan Terhadap Pengelolaan Keuangan Mahasiswa Fakultas Ekonomi Angkatan 2021 Universitas Pendidikan Ganesha - dewi, Kadek Irna; Arya Dharmayasa, I Putu (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The aim of this research is to identify how parents' socio-economic status and financial literacy influence student decision-making about their personal finances among the Class of 2021 at the Faculty of Economics, University of Education, Ganesha. This research uses a causal research design and relies on quantitative data. A questionnaire approach was used to collect data for this investigation. Two hundred sixty five students were surveyed out of a potential seven hundred eighty nine from the Faculty of Economics of Ganehsa University of Education Batch 2021. Deliberate sampling was used for data collection. This research includes a series of statistical tests which include multiple linear regression tests, t tests, f tests, and classical assumption tests. The findings of this research indicate that (1) the socio-economic status of the parents and (2) the financial literacy of the parents has a significant positive effect on the financial management of their children, and (3) the socio-economic status of the parents alone has no effect on financial management. An X1 value of 0.263 indicates that an increase in X1 will result in an increase in Y, and an X2 value of 0.303 indicates an increase in X2 will result in an increase in Y, this can be seen from the results of multiple linear regression. H1 there is acceptance because the significance value of the t-test does not exceed 0.05 for the variable of parents' socioeconomic status; H2 is accepted because the significance value of the t-test does not exceed 0.05 for the financial literacy variable; and H3 there is acceptance because the significance value of the f-test does not exceed 0.05. Keywords : Socio-economic status; Financial literacy; financial management.